Two cell types in rat substantia nigra zona compacta distinguished by membrane properties and the actions of dopamine and opioids - Lacey, MG (J Neurosci, 1989)
Intracellular recordings were made from 475 rat substantia nigra zona compacta neurons in vitro. The region from which recordings were made was rich in catecholamine fluorescence. Two groups of neuron, termed principal neurons (95% of the total) and secondary neurons (5% of the total) were clearly distinguishable according to one or more of the following 4 electrophysiological properties. Secondary neurons (23 cells) (1) fired spontaneous action potentials at frequencies greater than 10 Hz, or were quiescent (30%); (2) had action potentials less than 1 msec in duration; (3) did not show time-dependent inward rectification with step hyperpolarization; and (4) had slope conductances of about 4 nS (between -75 and -90 mV). In contrast, principal neurons (1) fired spontaneous action potentials in the range 1–8 Hz, or were quiescent (33%); (2) had action potentials greater than 1 msec in duration; (3) showed pronounced time-dependent inward rectification; and (4) had steady-state membrane slope conductances of around 22 nS (between -75 and -90 mV). Secondary cells were not affected by dopamine but were hyperpolarized by baclofen, GABA, and the mu opioid receptor agonist Tyr-D-Ala-Gly-MePhe-Gly-ol (DAGO). On the other hand, dopamine and baclofen inhibited firing and/or hyperpolarized all principal cells tested, but mu or delta opioid receptor agonists had no effect. The properties of these 2 cell types broadly correspond with those described by electrophysiological studies in vivo, in which case the majority, or principal, cells are believed to be dopaminergic.(ABSTRACT TRUNCATED AT 250 WORDS)